A Comparison between the Effects of Glucantime, Topical Trichloroacetic Acid 50% plus Glucantime, and Fractional Carbon Dioxide Laser plus Glucantime on Cutaneous Leishmaniasis Lesions - Fariba Jaffary; Mohammad Ali Nilforoushzadeh; Amirhossein Siadat; Elaheh Haftbaradaran; Nazli Ansari; Elham Ahmadi (Dermatology Research and Practice)
Background. Cutaneous leishmaniasis is an endemic disease in Iran. Pentavalent antimonial drugs have been the first line of therapy in cutaneous leishmaniasis for many years. However, the cure rate of these agents is still not favorable. This study was carried out to compare the efficacies of intralesional glucantime with topical trichloroacetic acid 50% (TCA 50%) + glucantime and fractional carbon dioxide laser + glucantime in the treatment of cutaneous leishmaniasis. Methods. A total of 90 patients were randomly divided into three groups of 30 to be treated with intralesional injection of glucantime, a combination of topical TCA 50% and glucantime, or a combination of fractional laser and glucantime. The overall clinical improvement and changes in sizes of lesions and scars were assessed and compared among three groups. Results. The mean duration of treatment was 6.1±2.1 weeks in all patients (range: 2–12 weeks) and 6.8±1.7, 5.2±1.0, and 6.3±3.0 weeks in glucantime, topical TCA plus glucantime, and fractional laser plus glucantime groups, respectively (P=0.011). Complete improvement was observed in 10 (38.5%), 27 (90%), and 20 (87%) patients of glucantime, glucantime + TCA, and glucantime + laser groups, respectively (P<0.001). Conclusion. Compared to glucantime alone, the combination of intralesional glucantime and TCA 50% or fractional CO2 laser had significantly higher and faster cure rate in patients with cutaneous leishmaniasis.